Integrated farming system approach increases profits of a farmer - Singh, Dinesh Kumar; Singh, Rohitashav; Singh, Gaurav Deep (Indian Farming, 2018)
Mr Nandan Singh, farmer, has increased from ` 39,626 (during benchmark year 2012-13) to ` 1,17,775 during second year 2014-15 his income. Highest increase of ` 55,929 was observed in crop module, additional returns of ` 16,375 was recorded in product diversification module whereas in case of livestock module net returns have increased from the benchmark year by ` 13,195.